Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By using the positive electrode active material NaxMnaFebMcNdO2+δ-eFe in sodium ion batteries, the covalent stable structure of strong oxygen and cation bonding is used to solve the problems of poor first-effect and cycling performance of existing sodium ion batteries, and a higher Battery capacity retention and service life.
Patent Information
- Application Number
- CN202310728659.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
The existing sodium ion batteries containing layered transition metal oxides have poor first-effect and cycling performance, mainly due to the instability of the structure during the de-embedding process, resulting in low battery capacity retention.
A positive electrode active material NaxMnaFebMcNdO2+δ-eFe is used, where M ions include Ni2+, Ni3+, Cu2+, Cu+, Zn2+, Mg2+, etc. The N ion potential is greater than or equal, and the bond covalent between cation and oxygen is strong and stable. Material structure, inhibit side reactions, and improve battery first-effect and cycling performance. The material is prepared by calcining or co-precipitation to ensure structural stability.
It significantly improves the first-effect and cycling performance of the battery, extends the service life of the battery, enhances the capacity retention rate, and solves the problem of structural instability.
Smart Images

Figure CN119170794A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal, wind and solar power stations, but are also widely used in electric transportation vehicles such as electric bicycles, electric motorcycles, electric cars, as well as in military equipment, aerospace and other fields.
[0003] Sodium ion battery is a kind of secondary battery, and layered transition metal oxide is a commonly used positive electrode active material for sodium ion battery. However, the first efficiency and cycle performance of existing sodium ion batteries containing layered transition metal oxide are poor.
[0004] Public Content
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to solve the problem of low first efficiency and cycle performance of the battery containing the positive electrode active material.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material comprises:
[0007] Na x Mn a Fe b M c N d O 2+δ-e F e ,
[0008] 0.5≤x≤1.1, a≥0, b≥0, c≥0, d>0, a+b+c+d=1, -0.1≤δ≤0.1, e≥0, M ions include Ni 2+ 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ Mg 2+ , Y 3+ ,La 3+ 、In 3+ , Sb 3+ , Li + Sn 2+ and Ag + At least one of B i is the molar fraction of the cation, I i is the ionic potential of the cation in units of The cations include manganese ions, iron ions, M ions and N ions, and the ion potential of the N ions is greater than or equal to
[0009] The positive electrode active material of the present application has a stable structure during the sodium insertion and extraction process, thereby improving the initial efficiency and cycle performance of the battery.
[0010] In some embodiments of the present application, Thereby, the initial efficiency and cycle performance of the battery can be improved.
[0011] In some embodiments of the present application, the N ions include B 3+ 、Ti 4+ 、Al 3+ 、Si 4+ Sn 4+ , Sb 5+ 、Zr 4+ and Nb 5 + At least one of, optionally, the N ions include B 3+ 、Ti 4+ 、Zr 4+ and Al 3+ At least one of the above. Thus, the first efficiency and cycle performance of the battery can be improved.
[0012] In some embodiments of the present application, the M ions include Ni 2+ 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ and Mg 2+ At least one of .
[0013] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: x is 0.7≤x≤1, and can be optionally 0.8≤x≤1; a is 0.3≤a≤0.7, and can be optionally 0.35≤a≤0.55; b is 0.1≤b≤0.4, and can be optionally 0.2≤b≤0.3; c is 0.2≤c≤0.5, and can be optionally 0.3≤c≤0.4; d is 0.005≤d≤0.1, and can be optionally 0.01≤d≤0.05; δ is -0.05≤δ≤0.05, and can be optionally -0.02≤δ≤0.02; e is 0≤e≤0.01, and can be optionally 0.001≤e≤0.005.
[0014] In some embodiments of the present application, 0.005≤d / (a+b+c)≤0.1, and may be 0.01≤d / (a+b+c)≤0.05. Thus, the first efficiency and cycle performance of the battery can be improved.
[0015] In some embodiments of the present application, the phase state of the positive electrode active material includes an O3 phase, and the space group includes The interlayer distance is 0.53nm-0.54nm, which can increase the capacity of the battery.
[0016] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions:
[0017] The positive electrode active material D v 50 is 2μm-30μm, optional is 4μm-12μm;
[0018] The specific surface area of the positive electrode active material is 0.1 m 2 / g-2m 2 / g, optional 0.3m 2 / g-1m 2 / g;
[0019] The compaction density of the positive electrode active material under 8 tons of pressure is 3g / cm 3 -5g / cm 3 , optional 3.5g / cm 3 -4.5g / cm 3 .
[0020] Therefore, when the D of the positive electrode active material v 50. When at least one of the specific surface area and the compaction density is within the above range, the conduction distance of Na ions in the positive electrode active material is short and the surface side reactions are few, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0021] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0022] Mixing a Na source, a Fe source, a Mn source, an M source, and a N source to obtain a precursor;
[0023] The precursor is calcined to obtain a positive electrode active material.
[0024] Therefore, the present application can prepare the above-mentioned positive electrode active material with excellent structural stability, thereby improving the first efficiency and cycle stability of the battery.
[0025] The third aspect of the present application provides another method for preparing the positive electrode active material described in the first aspect, comprising:
[0026] Mixing the Fe source, the Mn source, the M source and the N source with water to obtain a mixed solution;
[0027] reacting the mixed solution with a precipitant to obtain a precursor;
[0028] The precursor is mixed with a Na source and calcined to obtain a positive electrode active material.
[0029] Therefore, the present application can prepare the above-mentioned positive electrode active material with excellent structural stability, thereby improving the first efficiency and cycle stability of the battery.
[0030] The fourth aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application, the positive electrode active material prepared by the method described in the second aspect, or the positive electrode active material prepared by the method described in the third aspect.
[0031] The fifth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the fourth aspect of the present application. Thus, the battery has an excellent capacity retention rate.
[0032] A sixth aspect of the present application provides an electrical device, which includes the battery described in the fifth aspect.
[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0035] Figure 1 is a schematic structural diagram of a battery according to one embodiment of the present application;
[0036] Figure 2 is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0037] Figure 3 is a schematic structural diagram of a battery pack according to an embodiment of the present application;
[0038] Figure 4 yes Figure 3 Exploded diagram of
[0039] Figure 5 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source;
[0040] Figure 6 It is a comparison diagram of the charge and discharge curves of the button cells prepared in Example 1 and Comparative Example 1 at the first cycle of 10 mA / g;
[0041] Figure 7This is a comparison chart of the capacity retention rates of button batteries prepared in Example 1 and Comparative Example 1.
[0042] Description of reference numerals:
[0043] 1: Secondary battery; 2: Battery module; 3: Battery pack; 4: Upper case; 5: Lower case. DETAILED DESCRIPTION
[0044] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0045] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0046] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0047] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0049] With the technological development and increasing demand for electric vehicles and rechargeable mobile devices, secondary batteries, as a representative of the new energy field, have also seen rapid development in related research. Compared with traditional lithium-ion batteries, sodium-ion batteries have a strong price advantage and have broad application prospects in large-scale power storage systems.
[0050] Layered metal oxides have become one of the popular positive active materials for sodium ion batteries due to their high electrical conductivity, high energy density, large capacity and long cycle life. Before the battery is charged and discharged, the sodium content in the layered metal oxide is relatively high, and there are positively charged sodium ions between oxygen and oxygen, which shield the negative electrical repulsion between oxygen and oxygen. As the first charge progresses, the sodium ions on the surface of the layered metal oxide are released, and the negative electrical repulsion between oxygen and oxygen increases. The layered metal oxide undergoes irreversible structural changes, which reduces the number of sodium embedding sites in the layered metal oxide, resulting in a decrease in the first efficiency of the battery. At the same time, as the negative electrical repulsion between oxygen and oxygen in the layered metal oxide increases, its local structure becomes unstable and is prone to reconstruction to form new phases, such as rock salt phase or spinel phase. At the same time, after the sodium ions are reduced, the activity of oxygen will also increase, and it is easy to react with the electrolyte, resulting in the loss of cations and oxygen ions, forming cracks, thereby reducing the cycle performance of the battery.
[0051] In the present application, the positive electrode active material includes an ion potential greater than or equal to N ions, and manganese ions, iron ions, M ions and N ions meet The bonding covalency of cations and oxygen in the obtained positive electrode active material is strong, and the interaction is strong, which can effectively stabilize the structural changes of the positive electrode active material during the sodium insertion and extraction process, thereby improving the initial efficiency of the battery. At the same time, due to the strong interaction between cations and oxygen in the obtained positive electrode active material, the repulsive force between oxygen and oxygen is weak, making the structure of the positive electrode active material stable, and the activity of oxygen is weakened, thereby inhibiting the side reaction between the layered oxide and the electrolyte, and improving the battery cycle performance.
[0052] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0053] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising:
[0054] Nax Mn a Fe b M c N d O 2+δ-e F e ,
[0055] 0.5≤x≤1.1, a≥0, b≥0, c≥0, d>0, a+b+c+d=1, -0.1≤δ≤0.1, e≥0, M ions include Ni 2+ 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ Mg 2+ , Y 3+ ,La 3+ 、In 3+ , Sb 3+ , Li + Sn 2+ and Ag + At least one of B i is the molar fraction of the cation, I i is the ionic potential of the cation in units of The cations include manganese ions, iron ions, M ions and N ions, and the ion potential of the N ions is greater than or equal to
[0056] The present application at least includes the following beneficial effects: the positive electrode active material includes an ion potential greater than or equal to N ions, and manganese ions, iron ions, M ions and N ions meet The bonding covalency of cations and oxygen in the obtained positive electrode active material is strong, and the interaction is strong, which can effectively stabilize the structural changes of the positive electrode active material during the sodium insertion and extraction process, thereby improving the initial efficiency of the battery. At the same time, due to the strong interaction between cations and oxygen in the obtained positive electrode active material, the repulsive force between oxygen and oxygen is weak, making the structure of the positive electrode active material stable, and the activity of oxygen is weakened, thereby inhibiting the side reaction between the layered oxide and the electrolyte, and improving the battery cycle performance.
[0057] In this application, the ionic potential of the cation I i Defined as cation charge number / cation radius, where the cation charge number is equal to its valence and the unit of cation radius is B iis the molar fraction of cations, which is equal to the molar number of cations in the positive electrode active material / (molar number of manganese ions a+molar number of iron ions b+molar number of M ions c+molar number of N ions d)×100%, wherein the molar number of manganese ions a+molar number of iron ions b+molar number of M ions c+molar number of N ions d=1, and Σ represents addition, for example, ΣB in the present application i ×I i 4 =B Mn ×I Mn 4 +B Fe ×I Fe 4 +B M ×I M 4 +B n ×I n 4 .
[0058] In some embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e middle For example In some other embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e middle Therefore, in this application, the positive electrode active material has an ion potential greater than or equal to N ions and cations (including manganese ions, iron ions, M ions and N ions) ΣB i ×I i 4 When the above conditions are met, the bonding covalency between cations and oxygen in the obtained positive electrode active material is strong, the interaction is strong, and the structural changes of the positive electrode active material during the sodium insertion and extraction process can be effectively stabilized, thereby improving the initial efficiency of the battery. At the same time, due to the strong interaction between cations and oxygen in the obtained positive electrode active material, the repulsive force between oxygen and oxygen is weak, making the structure of the positive electrode active material stable, and the activity of oxygen is weakened, thereby inhibiting the side reaction between the layered oxide and the electrolyte, and improving the battery cycle performance.
[0059] In some embodiments of the present application, the above-mentioned positive electrode active material Nax Mn a Fe b M c N d O 2+δ-e F e Where x can be 0.5≤x≤1.1, for example, 0.6≤x≤1.1, 0.7≤x≤1, 0.8≤x≤1.1, 1≤x≤1.1, etc. Thus, the positive electrode active material includes the sodium element in this content, so that the battery has a higher capacity. In other embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Here x can be 0.7≤x≤1, for example, 0.8≤x≤1.
[0060] It should be noted that in the positive electrode sheet, battery or electrical device, as the battery undergoes formation and circulation processes, sodium ions will be consumed, so the measured sodium content x in the positive electrode active material may be less than 1. At the same time, if the positive electrode sheet and the negative electrode sheet use a sodium supplement, the measured sodium content x in the positive electrode active material may be greater than 1 after the battery undergoes formation and circulation processes.
[0061] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ -eF e Where a can be a≥0, for example, 0.001≤a<1, 0.005≤a≤0.9, 0.1≤a≤0.8, 0.2≤a≤0.7, 0.3≤a≤0.6, 0.4≤a≤0.5, etc. Therefore, the positive electrode active material includes this content of manganese, which can effectively improve the structural stability of the positive electrode active material and improve the cycle stability of the battery containing it. In some other embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Here, a can be 0.3≤a≤0.7, for example, 0.35≤a≤0.55.
[0062] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Feb M c N d O 2+δ-e F e b can be b≥0, for example, 0.001≤b<1, 0.005≤b≤0.9, 0.1≤b≤0.8, 0.2≤b≤0.7, 0.3≤b≤0.6, 0.4≤b≤0.5, etc. Therefore, the positive electrode active material includes this content of Fe, which can increase the specific capacity of the material. In some other embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Here b can be 0.1≤b≤0.4, for example, 0.2≤b≤0.3.
[0063] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e The M ions may include Ni 2+ 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ Mg 2+ , Y 3+ ,La 3+ 、In 3+ , Sb 3+ , Li + Sn 2+ and Ag + In some other embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e The M ions may include Ni 2+ 、Ni 3+ , Cu 2 + , Cu + 、Zn 2+ and Mg 2+ At least one of .
[0064] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mna Fe b M c N d O 2+δ-e F e Where c is 0≤c, for example, 0.001≤c<1, 0.005≤c≤0.9, 0.1≤c≤0.8, 0.2≤c≤0.7, 0.3≤c≤0.6, 0.4≤c≤0.5, etc. Thus, the positive electrode active material includes the M ions in this content, which can improve the structural stability of the material. In other embodiments of the present application, the positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Here, c can be 0.2≤c≤0.5, for example, 0.3≤c≤0.4.
[0065] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e The ionic potential of N ions in Therefore, in this application, the positive electrode active material has an ion potential greater than or equal to N ions and cations (including manganese ions, iron ions, M ions and N ions) ΣB i ×I i 4 When the above conditions are met, the bonding covalency between cations and oxygen in the obtained positive electrode active material is strong, the interaction is strong, and the structural changes of the positive electrode active material during the sodium insertion and extraction process can be effectively stabilized, thereby improving the initial efficiency of the battery. At the same time, due to the strong interaction between cations and oxygen in the obtained positive electrode active material, the repulsive force between oxygen and oxygen is weak, making the structure of the positive electrode active material stable, and the activity of oxygen is weakened, thereby inhibiting the side reaction between the layered oxide and the electrolyte, and improving the battery cycle performance.
[0066] As an example, the N ions include B 3+ 、Ti 4+ 、Al 3+ 、Si 4+ Sn 4+ , Sb 5+ 、Zr 4+ and Nb 5+ In some other embodiments of the present application, the N ions include B 3+ 、Ti 4+、Zr 4+ and Al 3+ At least one of .
[0067] The ionic potentials of common ions are shown in Table 1:
[0068] Table 1 Ionic potentials of common ions
[0069]
[0070]
[0071] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Where d is d>0, for example, 0.001≤c≤1, 0.005≤c≤0.9, 0.1≤c≤0.8, 0.2≤c≤0.7, 0.3≤c≤0.6, 0.4≤c≤0.5. In some other embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Where d is 0.005≤d≤0.1, for example, 0.01≤d≤0.05. Thus, by adding the N ions in the positive electrode active material, the cations (including manganese ions, iron ions, M ions and N ions) ΣB i ×I i 4 When the above conditions are met, the bonding covalency between cations and oxygen in the obtained positive electrode active material is strong, the interaction is strong, and the structural changes of the positive electrode active material during the sodium insertion and extraction process can be effectively stabilized, thereby improving the initial efficiency of the battery. At the same time, due to the strong interaction between cations and oxygen in the obtained positive electrode active material, the repulsive force between oxygen and oxygen is weak, making the structure of the positive electrode active material stable, and the activity of oxygen is weakened, thereby inhibiting the side reaction between the layered oxide and the electrolyte, and improving the battery cycle performance.
[0072] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e0.005≤d / (a+b+c)≤0.1, for example, 0.007≤d / (a+b+c)≤0.1, 0.01≤d / (a+b+c)≤0.095, 0.015≤d / (a+b+c)≤0.09, 0.02≤d / (a+b+c)≤0.085, 0.025≤d / (a+b+c)≤0.08, 0.03≤d / (a+b+c)≤0.075, 0.035≤d / (a+b+c)≤0.07, 0.04≤d / (a+b+c)≤0.065, 0.045≤d / (a+b+c)≤0.06, 0.05≤d / (a+b+c)≤0.055, etc. In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e 0.01≤d / (a+b+c)≤0.05. Therefore, the molar amount of N in the positive electrode active material of the present application and the sum of the molar amounts of Mn ions, Fe ions and M ions satisfy the above relationship, which can improve the structural stability of the positive electrode active material, thereby improving the first efficiency and cycle stability of the battery.
[0073] In some embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F e Where δ is -0.1≤δ≤0.1, and e is e≥0, for example, -0.09≤δ≤0.09, -0.08≤δ≤0.08, -0.07≤δ≤0.07, -0.06≤δ≤0.06, -0.05≤δ≤0.05, -0.04≤δ≤0.04, -0.03≤δ≤0.03, -0.02≤δ≤0.02, -0.01≤δ≤0.01, -0.01≤δ≤0, 0≤δ≤0.01, etc., 0.01≤e≤0.09, 0.02≤e≤0.08, 0.03≤e≤0.07, 0.04≤e≤0.06, 0.05≤e≤0.06, etc. In some other embodiments of the present application, the above-mentioned positive electrode active material Na x Mn a Fe b M c N d O 2+δ-e F eHere, the value of δ is -0.05≤δ≤0.05, for example, -0.02≤δ≤0.02; the value of e is 0≤e≤0.01, for example, 0.001≤e≤0.005.
[0074] Specifically, doping the positive electrode active material with this content of F at the oxygen position in the present application can effectively stabilize the oxygen in the positive electrode active material, thereby reducing the structural damage caused by lattice oxygen release in the positive electrode active material, improving the stability of the material, and further improving the cycle stability of the battery.
[0075] It should be noted that in the positive electrode sheet, battery or electrical device, since the battery undergoes cycles and other processes, there is a loss of oxygen in the positive electrode active material, so the measured oxygen content 2+δ-e in the positive electrode active material may be less than 2.
[0076] In some embodiments of the present application, the phase state of the positive electrode active material includes an O3 phase, and the space group includes The interlayer spacing is 0.53nm-0.54nm, for example, the interlayer spacing can be 0.532nm-0.54nm, 0.535nm-0.54nm, 0.537nm-0.54nm, etc. Specifically, the formed O3 phase has a high Na content in the positive electrode active material, and can release more Na ions, so that the battery capacity is high.
[0077] It should be noted that the phase state, space group and interlayer spacing of the positive electrode active material in the present application can be characterized by X-ray diffraction.
[0078] Specifically, the interlayer spacing d of the 003 crystal plane of the positive electrode active material is 003 The space group test method includes: grinding the sample to be tested in an agate mortar in a dry room or glove box and then passing it through a 350-mesh sieve, taking an appropriate amount of the sieved sample and loading it into the middle of the groove of the sample rack so that the loose sample powder is slightly higher than the plane of the sample rack; taking a glass slide and gently pressing the sample surface to make the sample surface consistent with the frame plane after scraping it flat, and scraping off the excess powder. After the sample is prepared, a BruckerD8A_A25 X-ray powder diffractometer from Brucker AxS of Germany is used to measure the CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the angle corresponding to the 003 crystal plane is used. According to the Bragg equation 2d·sinθ=λ, and each unit cell of the 003 crystal plane contains three transition metal layers, the interlayer spacing d of the 003 crystal plane can be obtained. 003 By comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software, the space group of the sample can be confirmed. At the same time, in the XRD spectrum, the characteristic peak in the range of 40.5° to 42.5° indicates that the positive electrode active material is O3 phase.
[0079] In some embodiments of the present application, D of the positive electrode active material v 50 is 2 μm-30 μm, for example, D v 50 can be 2 μm-29 μm, 4 μm-28 μm, 5 μm-15 μm, 6 μm-14 μm, 8 μm-13 μm, 9 μm-12 μm, 10 μm-11 μm, etc. In other embodiments of the present application, the D of the positive electrode active material v 50 is 4μm-12μm.
[0080] In this application, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, for example, with reference to the standard GB / T 19077-2016, and measured using a laser particle size analyzer (such as Malvern Master Size 3000).
[0081] In some embodiments of the present application, the specific surface area of the positive electrode active material is 0.1 m 2 / g-2m 2 / g, for example, the specific surface area of the positive electrode active material can be 0.1m 2 / g-1.5m 2 / g,0.2m 2 / g-1m 2 / g,0.3m 2 / g-0.8m 2 / g,0.3m 2 / g-0.5m 2 In some other embodiments of the present application, the specific surface area of the positive electrode active material is 0.3 m 2 / g-1m 2 / g.
[0082] In the present application, the specific surface area of the positive electrode active material can be tested by referring to the following method: using the American Micromeritics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390, take about 7g of the sample and put it into a 9cc long tube with a bulb, degas at 200℃ for 2h, and then put it into the main unit for testing to obtain the BET (specific surface area) data of the positive electrode active material.
[0083] In some embodiments of the present application, the compaction density of the positive electrode active material at a pressure of 300 MPa is 3.0 g / cm 3 -5.0g / cm 3 For example, the compaction density of the positive electrode active material at a pressure of 300 MPa can be 3.0 g / cm 3 -4.9g / cm 3, 3.2g / cm 3 -4.8g / cm 3 , 3.5g / cm 3 -4.5g / cm 3 , 3.7g / cm 3 -4.2g / cm 3 , 4g / cm 3 -4.2g / cm 3 In some embodiments of the present application, the compaction density of the positive electrode active material under a pressure of 300 MPa is 3 g / cm 3 -4g / cm 3 .
[0084] In the present application, "compacted density" has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, the following test method can be used: a certain amount of powder m is placed in a special compaction mold, the mold is placed on a compaction density instrument, a pressure of 300 MPa is set, and the volume v of the powder under a pressure of 300 MPa is measured on the equipment. The compacted density is calculated by density = mass m / volume v (specific reference GB / T24533-2009).
[0085] Specifically, when the D of the positive electrode active material of the present application is v 50. When at least one of the specific surface area and the compaction density under a pressure of 300 MPa is within the above range, the conduction distance in the positive electrode active material is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0086] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0087] S100: Mix Na source, Fe source, Mn source, M source and N source to obtain a precursor
[0088] In some embodiments of the present application, a Na source, a Fe source, a Mn source, an M source and a N source are mixed to obtain a precursor, which is then mixed according to the above-mentioned positive electrode active material composition.
[0089] It should be noted that, due to the loss of Na source in the subsequent calcination process, the amount of Na added will be slightly higher than the required Na content in the above-mentioned positive electrode active material composition.
[0090] The Na source, Fe source, Mn source, M source and N source in the present application are conventional materials in the field, and those skilled in the art can select them according to actual conditions. For example, the Na source may include at least one of Na2CO3, NaHCO3, NaOH and Na2O2; the Fe source may include at least one of FeO, Fe2O3 and Fe3O4; the Mn source may include at least one of Mn2O3, Mn3O4, MnO and MnO2; the M source may include at least one of an oxide of M, a salt containing M and other compounds; the N source may include at least one of an oxide of N, a salt containing N and other compounds.
[0091] It should be noted that if it is necessary to dope the positive electrode active material with the element F, at least one of the Na source, Fe source, Mn source, M source and N source adopts at least one of its corresponding fluorine-containing salts and other compounds, such as sodium fluoride, iron fluoride, iron fluoride, manganese fluoride, M fluoride (fluoride salt of M) and N fluoride (fluoride salt of N).
[0092] S200: calcining the precursor
[0093] In some embodiments of the present application, the precursor obtained above is placed in a muffle furnace and calcined in an air atmosphere, and then cooled to room temperature and mechanically crushed to obtain the positive electrode active material, wherein the calcination temperature can be 600℃-1200℃, for example, it can be 600℃-1100℃, 700℃-1000℃, 800℃-900℃, etc., and the insulation time is 10h-20h, for example, it can be 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0094] In addition, as needed, the precursor can be pre-calcined and kept warm before calcining the precursor. The pre-calcination temperature can be 600℃-900℃, for example, 600℃-850℃, 650℃-800℃, 600℃-750℃, 550℃-700℃, 500℃-650℃, 550℃-600℃, etc. The insulation time is 10h-20h, for example, 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0095] Therefore, the solid phase method can be used to prepare the above-mentioned positive electrode active material with stable structure, thereby improving the initial efficiency and cycle stability of the battery.
[0096] The third aspect of the present application provides another method for preparing the positive electrode active material described in the first aspect, comprising:
[0097] Sa: Mix Fe source, Mn source, M source and N source with water to obtain a mixed solution
[0098] In some embodiments of the present application, the Fe source, the Mn source, the M source and the N source are mixed with water to obtain a mixed solution, and the positive electrode active material composition is mixed with water to obtain a mixed solution.
[0099] It should be noted that the Fe source, Mn source, M source and N source in the present application are conventional materials in the field, and those skilled in the art can select them according to actual conditions. For example, the Fe source may include at least one of ferric chloride, ferric sulfate and ferric nitrate; the Mn source may include at least one of manganese chloride, manganese sulfate and manganese nitrate; the M source may include at least one of chloride, sulfate and nitrate of M; and the N source may include at least one of chloride, sulfate and nitrate of N.
[0100] Sb: The mixed solution is reacted with a precipitant to obtain a precursor
[0101] In some embodiments of the present application, the mixed solution obtained in step Sa is reacted with a solution containing a precipitant to obtain a precursor, wherein the solution containing the precipitant includes at least one of hydroxide, carbonate and oxalate, for example, the solution containing the precipitant includes at least one of ammonia, carbonic acid and oxalic acid.
[0102] Sc: Mix the precursor with the Na source and calcine
[0103] In some embodiments of the present application, the obtained precursor and the Na source are mixed and ball-milled or mechanically stirred according to the above-mentioned positive electrode active material composition, and then placed in a muffle furnace for calcination, and then cooled to room temperature, and mechanically crushed to obtain the positive electrode active material, wherein the calcination temperature is 600°C-1200°C, for example, it can be 700°C-1100°C, 800°C-1000°C, 900°C-950°C, etc., the calcination atmosphere can be air or oxygen atmosphere, and the insulation time is 10h-20h, for example, it can be 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc. Wherein, the Na source can include at least one of Na2CO3, NaHCO3, NaOH and Na2O2.
[0104] It should be noted that, according to needs, before the precursor and Na source are mixed and calcined, the precursor Na source can be pre-calcined and kept warm in advance. The pre-calcination temperature can be 600℃-900℃, for example, 600℃-850℃, 650℃-800℃, 600℃-750℃, 550℃-700℃, 500℃-650℃, 550℃-600℃, etc., and the insulation time can be 10h-20h, for example, 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc.
[0105] In the present application, if the corresponding N source is water-insoluble, such as N oxide (N oxide), the N source is not added in step Sa, and the precursor is mixed with the Na source and the N source and sintered in step Sc.
[0106] It should be noted that if it is necessary to dope the positive electrode active material with the element F, at least one of the Na source, Fe source, Mn source, M source and N source adopts at least one of its corresponding fluorine-containing salts and other compounds, such as sodium fluoride, iron fluoride, manganese fluoride, M fluoride (fluoride salt of M) and N fluoride (fluoride salt of N).
[0107] It should be noted that, due to the loss of Na source during the calcination process, the amount of Na added will be slightly higher than the required Na content in the above-mentioned positive electrode active material composition.
[0108] Therefore, the coprecipitation method can be used to prepare the above-mentioned positive electrode active material with stable structure, thereby improving the initial efficiency and cycle stability of the battery.
[0109] The fourth aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0110] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0111] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0112] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0113] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) and polyvinyl alcohol (PVA).
[0114] These materials are all commercially available.
[0115] The fifth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the fourth aspect of the present application. Thus, the battery has an excellent capacity retention rate.
[0116] A battery is a battery that can be used again by recharging the active materials after discharge.
[0117] It is understandable that the battery proposed in this application is a sodium ion battery.
[0118] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0119] [Negative electrode]
[0120] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0121] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0122] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of sodium ion batteries can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include but is not limited to at least one of sodium metal, carbon material, alloy material, transition metal oxide and / or sulfide, phosphorus-based material, and titanate material. Specifically, the carbon material may include at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon material; the alloy material may include an alloy material formed by at least one of Si, Ge, Sn, Pb, and Sb; the general formula of the transition metal oxide and sulfide is M x N y , wherein M includes at least one of Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V, and N includes O or S; the phosphorus-based material may include at least one of red phosphorus, white phosphorus, and black phosphorus; the titanate material may include Na2Ti3O7, Na2Ti6O 13 、Na4Ti5O 12 、Li4Ti5O 12 At least one of NaTi2(PO4)3. These materials can be obtained through commercial channels.
[0123] The negative electrode active material layer may also optionally include a binder and a conductive agent. The conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bind the negative electrode active material and the binder to the negative electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0124] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0125] As an example, the binder may include at least one of styrene butadiene rubber (SBR), styrene butadiene rubber (SBCs), water-based acrylic resin, and carboxymethyl cellulose (CMC).
[0126] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, the present application is not limited thereto, and the present application may also use other materials that can be used as thickeners for negative electrode sheets of sodium ion batteries.
[0127] [Electrolyte]
[0128] The electrolyte may include an electrolyte salt and a solvent.
[0129] As an example, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate, and sodium bis(trifluoromethylsulfonyl)imide.
[0130] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0131] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0132] [Isolation film]
[0133] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0134] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 1 The secondary battery 1 is a square structure as an example.
[0135] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0136] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0137] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is packaged in the receiving cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.
[0138] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0139] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0140] In some embodiments, the batteries may be assembled into a battery module. The battery module may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0141] Figure 2 2 is an example of a battery module 2. Figure 2In the battery module 2, the plurality of secondary batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 1 may be fixed by fasteners.
[0142] The battery module 2 may further include a housing having a housing space, in which a plurality of secondary batteries 1 are housed. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0143] Figure 3 and 4 The battery pack 3 is used as an example. Figure 3 and 4 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0144] The sixth aspect of the present application provides an electrical device, which includes the battery described in the fifth aspect. Specifically, the battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0145] Figure 5 The electrical equipment is used as an example, and the electrical equipment includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0146] As another example, the electric device may include a mobile phone, a tablet computer, and a notebook computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0147] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0148] Example 1
[0149]
【NaNi 0.24 Fe 0.26 Mn 0.39 Mg 0.1 Si 0.01 O2 preparation].
[0150] A total of 30 g of Na2CO3, NiO, Fe2O3, Mn2O3, MgO and SiO2 were weighed according to a molar ratio of Na:Ni:Fe:Mn:Mg:Si of 1:0.24:0.26:0.39:0.1:0.01. The obtained sample was pre-ground in an agate mortar and added to a planetary ball mill for ball milling for 1 hour to obtain a precursor mixture. The obtained precursor mixture was then evenly placed in an open crucible, and then heated from room temperature to 950°C in a muffle furnace at a heating rate of 5°C / min, and kept at a constant temperature of 950°C for 15 hours. After natural cooling, the positive electrode active material NaNi 0.24 Fe 0.26 Mn 0.39 Mg 0.1 Si 0.01 O2.
[0151]
Preparation of positive electrode
[0152] NaNi 0.24 Fe 0.26 Mn 0.39 Mg 0.1 Si 0.01 O2, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a solvent NMP according to a mass ratio of 80:15:5 to form a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the surface of the positive electrode collector aluminum foil. After drying and cold pressing, it is punched into a disc with a diameter of 14 mm to obtain a positive electrode sheet.
[0153]
Preparation of negative electrode sheet
[0154] The negative electrode plate is made of metallic sodium.
[0155]
Preparation of electrolyte
[0156] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in equal volumes to obtain an organic solvent, and then NaClO4 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0157]
Isolation film
[0158] A porous polyethylene film was used as the separator.
[0159]
Preparation of button cell
[0160] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the prepared electrolyte is added to obtain a button battery.
[0161] The button cells containing positive electrode active materials of Examples 2-20 and Comparative Examples 1-4 are the same as Example 1 except for different parameters in the process of preparing the positive electrode active materials (see Table 1).
[0162] The compositions of the positive electrode active materials in the batteries of Examples 1-20 and Comparative Examples 1-4 of the present application are shown in Table 2.
[0163]
[0164]
[0165] The phase state, space group and interlayer spacing of the positive electrode active materials in Examples 1-20 and Comparative Examples 1-4, as well as the first efficiency and cycle performance of the obtained button cells were characterized. The characterization results are shown in Table 3.
[0166] Test methods:
[0167] (1) Phase state of positive electrode active material and interlayer spacing d of 003 crystal plane 003 And space group test:
[0168] In a dry room or glove box, grind the sample to be tested in an agate mortar and pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and put it in the middle of the groove of the sample rack so that the loose sample powder is slightly higher than the plane of the sample rack. Take a glass slide and gently press the sample surface to make the sample surface consistent with the frame plane after scraping it flat, and scrape off the excess powder. After the sample is prepared, use the Brucker D8A_A25 X-ray powder diffractometer of BruckerAxS Company in Germany to measure the CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the angle corresponding to the 003 crystal plane is used. According to the Bragg equation 2d·sinθ=λ, and each unit cell of the 003 crystal plane contains three transition metal layers, the interlayer spacing d of the 003 crystal plane can be obtained. 003 By comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software, the space group of the sample can be confirmed. At the same time, in the XRD spectrum, the characteristic peak in the range of 40.5° to 42.5° indicates that the positive electrode active material is O3 phase.
[0169] (2) First cycle coulombic efficiency test of button cell
[0170] At 25°C, the button cell is charged to 4.3V at a current density of 10mA / g, and the charge specific capacity C0 of the button cell is obtained. Then, the button cell is discharged to 1.5V at a current density of 10mA / g, and the discharge specific capacity C1 of the button cell is obtained. The first cycle coulomb efficiency of the battery = C1 / C0×100%.
[0171] (3) Cyclic performance test
[0172] At 25°C, the button cell was charged to 4.2V at a current density of 10mA / g, and then discharged to 1.5V at a current density of 10mA / g, to obtain the discharge capacity C2 of the button cell, and then the charge and discharge cycle was performed at a current density of 10mA / g for 50 cycles, and the discharge capacity C3 of the 50th cycle was obtained. The capacity retention rate of the battery after 50 cycles = C2 / C3×100%.
[0173] Figure 6 It is a comparison diagram of the charge and discharge curves of the button cells prepared in Example 1 and Comparative Example 1 at the first cycle of 10 mA / g. It can be seen from the figure that the first cycle coulombic efficiency of the button cell of Example 1 is 98%, and the first cycle coulombic efficiency of the button cell of Comparative Example 1 is 81%. Obviously, the first cycle coulombic efficiency of the button cell of Example 1 is higher than that of the button cell of Comparative Example 1.
[0174] Figure 7 It is a comparison chart of the capacity retention rates of button batteries prepared in Example 1 and Comparative Example 1. It can be seen from the figure that the capacity retention rate of the battery in Example 1 is significantly better than that in Comparative Example 1 after 50 cycles.
[0175] Table 3
[0176]
[0177]
[0178] Conclusion: From the data in Table 3, it can be seen that the first cycle coulombic efficiency and the capacity retention rate of the batteries of Examples 1-20 are significantly higher than those of the batteries of Comparative Examples 1-4, which shows that the positive electrode active material of the present application includes an ion potential greater than or equal to N ions, and manganese ions, iron ions, M ions and N ions satisfy ΣB i ×I i 4 ≥1500, which can improve the first-cycle coulombic efficiency and cycle performance of the battery.
[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, It is characterized in that include: So x Mr a Feb b M c N d O 2+δ-e F e , 0.5≤x≤1.1, a≥0, b≥0, c≥0, d>0, a+b+c+d=1, -0.1≤δ≤0.1, e≥0, M ions include Ni 2 + 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ Mg 2+ , Y 3+ ,La 3+ 、In 3+ , Sb 3+ , Li + Sn 2+ and Ag + At least one of B i is the molar fraction of the cation, I i is the ionic potential of the cation in units of The cations include manganese ions, iron ions, M ions and N ions, and the ion potential of the N ions is greater than or equal to 2. The positive electrode active material according to claim 1, It is characterized in that 3. The positive electrode active material according to claim 1 or 2, It is characterized in that The N ions include B 3+ 、Ti 4+ 、Al 3+ 、Si 4+ Sn 4+ , Sb 5+ 、Zr 4+ and Nb 5+ At least one of, optionally, the N ions include B 3+ 、Ti 4+ 、Zr 4+ and Al 3+ At least one of .
4. The positive electrode active material according to any one of claims 1 to 3, It is characterized in that The M ions include Ni 2+ 、Ni 3+ , Cu 2+ , Cu + 、Zn 2+ and Mg 2+ At least one of .
5. The positive electrode active material according to any one of claims 1 to 4, It is characterized in that The positive electrode active material satisfies at least one of the following conditions: The value of x is 0.7≤x≤1, and can be 0.8≤x≤1; The value of a is 0.3≤a≤0.7, and can be 0.35≤a≤0.55; The value of b is 0.1≤b≤0.4, and can be 0.2≤b≤0.3; The value of c is 0.2≤c≤0.5, and can be 0.3≤c≤0.4; The value of d is 0.005≤d≤0.1, and can be selected as 0.01≤d≤0.05; The value of δ is -0.05≤δ≤0.05, and can be -0.02≤δ≤0.02; The value of e is 0≤e≤0.01, and can be selected as 0.001≤e≤0.
005.
6. The positive electrode active material according to any one of claims 1 to 5, It is characterized in that 0.005≤d / (a+b+c)≤0.1, which can be optionally 0.01≤d / (a+b+c)≤0.
05.
7. The positive electrode active material according to any one of claims 1 to 6, It is characterized in that The phase state of the positive electrode active material includes O3 phase, the space group includes R3m, and the interlayer spacing is 0.53nm-0.54nm.
8. The positive electrode active material according to any one of claims 1 to 7, It is characterized in that The positive electrode active material satisfies at least one of the following conditions: The positive electrode active material D v 50 is 2μm-30μm, optional is 4μm-12μm; The specific surface area of the positive electrode active material is 0.1 m 2 / g-2m 2 / g, optional 0.3m 2 / g-1m 2 / g; The compaction density of the positive electrode active material under a pressure of 300 MPa is 3 g / cm 3 -5g / cm 3 , optional 3g / cm 3 -4g / cm 3 .
9. A method for preparing the positive electrode active material according to any one of claims 1 to 8, It is characterized in that include: Mixing a Na source, a Fe source, a Mn source, an M source, and a N source to obtain a precursor; The precursor is calcined to obtain a positive electrode active material.
10. A method for preparing the positive electrode active material according to any one of claims 1 to 8, It is characterized in that include: Mixing the Fe source, the Mn source, the M source and the N source with water to obtain a mixed solution; reacting the mixed solution with a precipitant to obtain a precursor; The precursor is mixed with a Na source and calcined to obtain a positive electrode active material.
11. A positive electrode sheet, It is characterized in that The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 8 or the positive electrode active material prepared by the method according to claim 9 or 10.
12. A battery, It is characterized in that The battery comprises the positive electrode sheet according to claim 11.
13. An electrical device, It is characterized in that Comprising the battery as claimed in claim 12.
Citation Information
Patent Citations
Positive electrode active material for sodium-ion battery, sodium-ion battery made of same, battery module, battery pack, and device
CN112670497A
Positive electrode active material for sodium-ion battery
CN113454031A
Layered oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered oxide positive electrode material
CN115799493A
Positive electrode active material and preparation method thereof, positive electrode plate and sodium ion battery
CN115810748A
